2001
DOI: 10.1142/s0218271801000883
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Evolution of Strongly Magnetized Quark Core in a Newborn Neutron Star

Abstract: The chemical evolution of nascent quark matter core in a newborn compact neutron star is studied in presence of a strong magnetic field.The effective rate of strange quark production in degenerate quark matter core in presence of strong magnetic fields is obtained. The investigations show that in presence of strong magnetic fields a quark matter core becomes energetically unstable and hence a deconfinement transition to quark matter at the centre of a compact neutron star *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The matter in the star may contain only deconfined quarks, a phenomenon known as a SS, or hyperons may appear, making hyperonic matter. The effect of magnetic field on quark matter using the Massachusetts Institute of Technology (MIT) bag model has been studied earlier (Chakrabarty 1996; Ghosh & Chakrabarty 2001a,b; Felipe et al 2008). There are other models of quark matter with phenomenological density‐dependent quark masses (Fowler, Raha & Weiner 1981; Chakrabarty 1991; Dey et al 1998; Li, Xu & Lu 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The matter in the star may contain only deconfined quarks, a phenomenon known as a SS, or hyperons may appear, making hyperonic matter. The effect of magnetic field on quark matter using the Massachusetts Institute of Technology (MIT) bag model has been studied earlier (Chakrabarty 1996; Ghosh & Chakrabarty 2001a,b; Felipe et al 2008). There are other models of quark matter with phenomenological density‐dependent quark masses (Fowler, Raha & Weiner 1981; Chakrabarty 1991; Dey et al 1998; Li, Xu & Lu 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of compact neutron stars, the phase transition from neutron matter to quark matter, which may occur at the core region, is also affected by strong quantizing magnetic field. It has been shown that a first order phase transition initiated by the nucleation of quark matter droplets is absolutely forbidden if the magnetic field strength ∼ 10 15 G at the core region [11,12]. However, a second order phase transition is allowed, provided the magnetic field strength < 10 20 G. This is of course too high to achieve at the core region.…”
Section: Introductionmentioning
confidence: 99%
“…The studies on the effect of strong magnetic field on various physical processes, relevant for these exotic objects have been reported during the past few years. These studies are mainly related to the equation of states of dense matter [7][8][9], elementary processesspecially weak and electromagnetic decays and reactions [10], quark-hadron phase transition [11][12][13], and transport coefficients of dense matter [14]. A few years ago we have shown explicitly that a first order quark-hadron phase transition is absolutely forbidden in presence of strong magnetic field (≥ a few times 10 15 Gauss [11,12]).…”
mentioning
confidence: 99%
“…We have designated d, ν e or νe , u and e by i = 1, 2, 3 and 4 respectively. In this moderately strong magnetic field strength, we have used conventional spinor solutions for the quarks and charge neutral neutrinos or anti-neutrinos, whereas for electron we have used [11,13,16]…”
mentioning
confidence: 99%
See 1 more Smart Citation